Impact of Education Provided by Nurses on Quality of Life, Anxiety, and Depression in Patients Receiving Hepatitis C Virus Therapy - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
The aim of this study was to determine the impact of education provided by a nurse on quality of life, anxiety, and depression in patients receiving hepatitis C virus (HCV) therapy. The total number of patients receiving HCV treatment was 25 patients (18 females and 7 males). Organized patient lectures addressed transmission routes of HCV, effects of virus on the liver, interferon treatment, treatment complications and care, and psychosocial problems faced by patients with HCV and their families. Lectures were followed by interviews in small groups including 3-4 patients each and repeated 3 months after. Data were collected by patient surveys, Hospital Anxiety-Depression Scale, and Short Form (SF)-36 Health Survey (SF-36). There were no significant differences between pre- and posteducation for the SF-36 domains, namely role physical, health perception, social functioning, role emotion, and mental health, whereas there were significant differences between pre- and posteducation for the SF-36 domains, namely physical function, bodily pain, and vitality. Pre-education depression and anxiety scores were higher than posteducation depression and anxiety scores. Specific educational programs provided by nurses improved patients' quality of life and decreased anxiety and depression in patients receiving HCV therapy. These findings support the importance of educational programs provided by nurses for HCV patients.
Keywords: RIBAVIRIN TREATMENT; HCV-INFECTION; INTERFERON; EXPERIENCE; MANAGEMENT; ADHERENCE; TRIAL